Investigation of neutrophilic peptides in periprosthetic tissue by matrix-assisted laser desorption ionisation time-of-flight imaging mass spectrometry - Gravius, Sascha; Randau, Thomas; Casadonte, Rita; Kriegsmann, Mark; Friedrich, Max J.; Kriegsmann, Jörg (International orthopaedics, 2015)
The accurate diagnosis of periprosthetic joint infection (PJI) relies on clinical investigation, laboratory parameters, radiological methods, sterile joint aspiration for synovial fluid leucocyte count and microbiological analysis and tissue sampling for histopathology. Due to the limits in specificity and sensitivity of these methods, molecular techniques and new biomarkers were introduced into the diagnostic procedure. Histological examination is related to the amount of neutrophils in the periprosthetic tissue in frozen sections and formalin-fixed paraffin embedded material (FFPE). However, the threshold of neutrophils per defined area of tissue among various studies is very inconsistent. Methods We have applied matrix-assisted laser desorption ionisation time-of-flight imaging mass spectrometry (MALDI IMS) to a total of 32 periprosthetic tissue samples of patients with PJI to detect peptides associated with areas of neutrophil infiltration. Results Specific peaks associated with a high amount of neutrophils were detected. Of these m/z peaks, four could be assigned to predictive neutrophil molecules. These peptides include annexin A1, calgizzarin (S100A11), calgranulin C (S100A12) and histone H2A. By MALDI IMS, these peptides could be shown to be co-localised with the infiltration of neutrophils in the immediate vicinity of the periprosthetic interface, whereas more distant areas did not show neutrophil invasion or infection-related peptides. Conclusions MALDI IMS is a new method allowing identification of neutrophil peptides in periprosthetic tissues and may be a surrogate for counting neutrophils as an objective parameter for PJI.
Published online: 3 October 2014
Gesehen am 21.09.2020